UPAYA PENCEGAHAN TINDAK PIDANA KORUPSI PENGADAAN BARANG DAN JASA PEMERINTAH MELALUI PENERAPAN PEMBELIAN LANGSUNG BERDASARKAN SISTEM KATALOG ELEKTRONIK (E-PURCHASING) - NS, Radhia Jatu (Prokons: Jurnal Teknik Sipil, 2020)
One form and effort of the government in tackling crime corruption in the case of goods and services procurement is by preparing and improve the governance of procurement of goods / services based on government electronic (E-Procurement) through the implementation of a direct purchasing system goods / services based on an electronic catalog (E-Purchasing). Deep problems This research is whether the form of applying a purchase through a catalog system e-Purchasing can prevent corruption and whether inhibiting factors for the application of E-Purchasing. Problem approach which is used is a normative juridical approach and empirical juridical approach.Primary data obtained through interviews with several sources while secondary data were obtained through literature study. Based on the results the research and discussion concluded that, the application of purchasing through Electronic catalog system (E-Purchasing) influences prevention efforts corruption in the procurement of goods / services. But in practice there is several inhibiting factors in the application of purchasing goods and services through electronic catalog system (E-Purchasing) including: law enforcement factors and factors of facilities / infrastructure or facilities that support law enforcement.Suggestions in this study are expected to be a strategy in response to actions criminal corruption in the procurement of goods / services if it will be done consistently with a preventive approach in the form of prevention by using the tools at outside of criminal law (non-penal), it is necessary to increase cooperation between Government Goods / Services Procurement Policy Agency (LKPP), provider, distributor of goods / services, and procurement manager.